Impact of participatory natural resource management research in cassava-based cropping systems in Vietnam and Thailand - Dalton, Timothy J.; Lilja, Nina; Johnson, Nancy L.; Howeler, Reinhardt H. (CAB International, 2007)
In South-east Asia, many of the poorest farmers live in areas with limited potential for crop production. Cassava (Manihot esculenta Crantz) is an important crop on these soils, because it is easy to grow, requires few external inputs and its roots and leaves can be used as human or animal feed. Cassava is also planted as an industrial crop for the production of animal feed and starch where market conditions are developed. The wide variety of end uses makes it a popular crop and an effective vehicle for improving the livelihood of poor upland farmers.